2018
DOI: 10.1128/iai.00280-18
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica Serovar Typhimurium CpxRA Two-Component System Contributes to Gut Colonization in Salmonella-Induced Colitis

Abstract: , a common cause of diarrhea, has to colonize the gut lumen to elicit disease. In the gut, the pathogen encounters a vast array of environmental stresses that cause perturbations in the bacterial envelope. The CpxRA two-component system monitors envelope perturbations and responds by altering the bacterial gene expression profile. This allows to survive under such harmful conditions. Therefore, CpxRA activation is likely to contribute to gut infection. However, the role of the CpxRA-mediated envelope stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 54 publications
(74 reference statements)
0
22
0
Order By: Relevance
“…To this end, we performed a CI experiment using the S . Tm invG ssaV avirulent strain, which is incapable of inducing the gut inflammation [ 47 ]. We first confirmed that a mutation of the invG gene had no effect on the cell division in vitr o ( S5 Fig ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To this end, we performed a CI experiment using the S . Tm invG ssaV avirulent strain, which is incapable of inducing the gut inflammation [ 47 ]. We first confirmed that a mutation of the invG gene had no effect on the cell division in vitr o ( S5 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…As S . Tm amiA and amiC expression is positively regulated by the CpxRA two-component system [ 57 ], the bacterial strains were grown under CpxRA-inducible conditions; i.e., high osmolarity (here, 0.5 M NaCl) [ 58 ] or the presence of antimicrobial peptide (here, 1 μg/ml polymyxin B) [ 47 , 59 ], and subjected to microscopy analysis. When grown in LB broth containing 0.5 M NaCl, in all cell configurations, the proportion of chains of GFP-expressing ssaV amiC and GFP-expressing ssaV amiA amiC strains were dramatically increased ( Fig 8A and 8B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To first demonstrate that our reporter strain retained virulence and to characterize the expression of SPI-1 in the mouse intestinal tract, a well-defined animal model, we performed a competition assay between the fluorescent reporter and the otherwise isogenic wild-type (WT) S. Typhimurium ATCC 14028s in mice. Streptomycintreated C57BL/6 mice were orally inoculated with an equal mixture of the two strains, and bacterial colonization of the ilea, ceca, liver, and spleen was quantified at 2 days postinfection, a time by which robust inflammation is observed in this model (24)(25)(26). We found that our reporter strain retained full virulence, colonizing both the intestine and systemic sites similarly to the wild-type organism ( Fig.…”
Section: Resultsmentioning
confidence: 84%